Integrated exposure assessment of sewage workers to genotoxicants: an urinary biomarker approach and oxidative stress evaluation - Al Zabadi, Hamzeh (BioMed Central, 2011)
BACKGROUND: Sewage workers are exposed to multiple chemicals among which many are suspected genotoxicants. Therefore, they might incur DNA damage and oxidative stress. We aimed to explore integrated urinary biomarkers, assessing the overall urine genotoxicity by in vitro comet and micronucleus assays and measuring urinary 8-oxo-2'-deoxyguanosine. METHODS: During three consecutive working days, polycyclic aromatic hydrocarbons and volatile organic compounds were sampled in workplace air of 34 sewage and 30 office workers, as indicators of airborne exposure. The last day, subjects collected their 24 hours urine. Genotoxicity of urinary extracts was assessed by comet and micronucleus assays on a HepG2 cell line. Using competitive enzymatic immunoassay we evaluated the 24 hours urinary 8-oxo-2'-deoxyguanosine excretion. Benzo(a)pyrene toxicity equivalent factors and inhalation unit risk for Benzo(a)pyrene and benzene were used to give an estimate of cancer risk levels. RESULTS: Workplace air concentrations of polycyclic aromatic hydrocarbons (e.g. 23.7 [range 2.4-104.6] ng.m(-3 )for fluoranthene) and volatile organic compounds (e.g. 19.1 ± 2.9 [standard error] μ.m(-3 )for benzene) were elevated in sewage compared to office workplaces (P < 0.01) and corresponded to an increased lifetime cancer risk. The urinary extracts of sewage workers showed higher genotoxicity (P < 0.001) than office workers. CONCLUSIONS: The integrated and non-specific urinary biomarkers of exposure showed that sewage workers experience exposure to mixtures of genotoxicants in the workplace.